Decrease of blood flow velocity in the middle cerebral artery after stellate ganglion block following aneurysmal subarachnoid hemorrhage: a potential vasospasm treatment? - Wendel, Christopher; Scheibe, Ricardo; Wagner, Sören; Tangemann, Wiebke; Henkes, Hans; Ganslandt, Oliver; Schiff, Jan-Henrik (Journal of neurosurgery, 2020)
OBJECTIVE Cerebral vasospasm (CV) is a delayed, sustained contraction of the cerebral arteries that tends to occur 3-14 days after aneurysmal subarachnoid hemorrhage (aSAH) from a ruptured aneurysm. Vasospasm potentially leads to delayed cerebral ischemia, and despite medical treatment, 1 of 3 patients suffer a persistent neurological deficit. Bedside transcranial Doppler (TCD) ultrasonography is used to indirectly detect CV through recognition of an increase in cerebral blood flow velocity (CBFV). The present study aimed to use TCD ultrasonography to monitor how CBFV changes on both the ipsi- and contralateral sides of the brain in the first 24 hours after patients have received a stellate ganglion block (SGB) to treat CV that persists despite maximum standard therapy. METHODS The data were culled from records of patients treated between 2013 and 2017. Patients were included if an SGB was administered following aSAH, whose CBFV was ≥ 120 cm/sec and who had either a focal neurological deficit or reduced consciousness despite having received medical treatment and blood pressure management. The SGB was performed on the side where the highest CBFV had been recorded with 8-10 ml ropivacaine 0.2%. The patient’s CBFV was reassessed after 2 and 24 hours. RESULTS Thirty-seven patients (male/female ratio 18:19), age 17-70 years (mean age 49.9 ± 11.1), who harbored 13 clipped and 22 coiled aneurysms (1 patient received both a coil and a clip, and 3 patients had 3 untreated aneurysms) had at least one SGB. Patients received up to 4 SGBs, and thus the study comprised a total of 76 SGBs. After the first SGB, CBFV decreased in 80.5% of patients after 2 hours, from a mean of 160.3 ± 28.2 cm/sec to 127.5 ± 34.3 cm/sec (p < 0.001), and it further decreased in 63.4% after 24 hours to 137.2 ± 38.2 cm/sec (p = 0.007). A similar significant effect was found for the subsequent SGB. Adding clonidine showed no significant effect on either the onset or the duration of the SGB. Contralateral middle cerebral artery (MCA) blood flow was not reduced by the SGB. CONCLUSIONS To the authors’ knowledge, this is the largest study on the effects of administering an SGB to aSAH patients after aneurysm rupture. The data showed a significant reduction in ipsilateral CBFV (MCA 20.5%) after SGB, lasting in about two-thirds of cases for over 24 hours with no major complications resulting from the SGB.